Arquitectura institucional: la naturaleza de la institución y su influencia en la arquitectura - Egúsquiza Berrocal, Fidel Fabricio (2013)
This paper seeks to show the relationship between the nature of the institution requesting a commission and the architectural response that we can give as professionals, trying to understand what other factors are involved, sometimes decisively, in architectural production. To make clear this relationship, three institutions of different kind have been selected in order to allow a comparative analysis between the architectural types that were generated for each case. These are: the cultural institution, the educational institution and the bank. This is a concern that comes along my practice, mainly institutional architecture, noticing the enormous complexity we face to shape our work and how professional quality is also defined when you learn to deal with all these factors to produce architecture.